Pengaruh Model Think Pair Share Berbantuan LKPD Diagram Scaffolding Terhadap Kemampuan Scientific Explanation Siswa SMP Pada Pembelajaran IPA - Nanda Tiara Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study investigates the effect of the Think Pair Share (TPS) learning model assisted by scaffolding diagram-based worksheets on students’ scientific explanation abilities in junior high school science. A quasi-experimental pretest-posttest control group design was used, involving an experimental class taught using TPS with scaffolding diagrams and a control class taught through direct instruction. Data were collected using a scientific explanation test based on the Claim, Evidence, and Reasoning (CER) framework and analyzed using N-gain and statistical tests. The results indicate that students in the experimental class showed greater improvement than those in the control class. Therefore, the TPS model assisted by scaffolding diagram worksheets positively influences students’ scientific explanation abilities.
FINALISASI oleh Arif 2026 Mei 20
Keywords: Scaffolding Diagram Worksheet; Science Learning; Scientific Explanation; Think Pair Share